A compact circuit-level model for single-event burnout in SiC power MOSFET devices. (1st December 2022) - Shen, Pei; Wang, Ying; Li, Xing-Ji; Yang, Jian-qun; Cao, Fei
Abstract: This paper presents a compact circuit-level model for single-event burnout (SEB) in silicon carbide (SiC) metal-oxide field-effect transistors (MOSFETs). Key parameters of the equivalent circuit model of the MOSFET are analyzed and determined in detail, including nonlinear parasitic drain-source capacitance and nonlinear parasitic gate-drain capacitance. The effect of the parasitic bipolar junction transistor is considered and an iteratively optimized double-exponential current source is used to simulate the transient power current generated by incident heavy ions. The equivalent circuit model of the MOSFET is verified by comparing the SPICE simulation curves, TCAD simulation curves, and the curves in the SiC power double trench MOSFET's datasheet (SCT3080KL). Then, the SEB is caused by heavy ions at various incident positions, linear energy transfer values, drain-source voltage ( V ds ), and gate-source voltage ( V gs ) using the TCAD and HSPICE simulations. Simulation results on the SPICE model coincide with the TCAD simulation results. Moreover, this compact model is used to predict the SEB threshold for devices with higher breakdown voltage ratings.